Outcomes of 44 Consecutive Complete Bilateral Cleft Lip and Palate Patients Treated with Secondary Alveolar Bone Grafting and Premaxillary Osteotomy. (May 2017) - Scott, Rupert; Scott, Julia; Stagnell, Sami; Robinson, Steve; Flood, Tim
Objective: To report the surgical outcomes of secondary alveolar bone grafting with premaxillary osteotomy in a single surgeon cohort of complete bilateral cleft lip and palate patients. Design: Retrospective review of 44 consecutive patients using hospital notes and radiographs. Setting: Single specialist cleft lip and palate center, UK. Patients: Consecutive patients with complete bilateral cleft lip and palate who were being treated with secondary alveolar bone grafting incorporating premaxillary osteotomy. Outcome Measures: Assessment of success of bone graft by Kindelan score; canine eruption; closure of fistulae and assessment of morbidity. Results: Between January 6, 2000, and August 8, 2013, 44 patients with complete BCLP underwent secondary ABG with a premaxillary osteotomy as a one-stage procedure. The mean follow-up was 7.3 years (range 1.4 to 14.6). Eighty-five percent of ABGs were successful (a Kindelan score of 1 or 2), and canine eruption was 89%. Failure of the ABG occurred in 7%. Fistulae recurrence rate was 11%, all of which were asymptomatic. No premaxillae were devitalized. Conclusion: Incorporating a premaxillary osteotomy into the secondary ABG surgical protocol can be a safe technique that gives excellent surgical exposure for fistula repair.